Enhancing EFL vocabulary learning with multimodal cues supported by an educational robot and an IoT-Based 3D book. (February 2022) - Lin, Vivien; Yeh, Hui-Chin; Huang, Huai-Hsuan; Chen, Nian-Shing
Abstract: Three-dimensional (3D) books, which feature interactive learning environments for immersing learners in situated learning, have proven to be an effective mediating tool for vocabulary acquisition. However, traditional 3D books lack affordances for two-way communication and multimodal language input for language learners. This study aims to apply multimodal cues in a task-based learning system consisting of an educational robot and a 3D book supported by the Internet of Things (IoT) to enhance EFL children's vocabulary learning. Two fourth graders participated in two phases of research (Exploratory and Enhancement Phases) separated by a six-month systematic enhancement period. In the Enhancement Phase, the two learners took pre- and post-tests on vocabulary recognition and oral production. Results showed a significant improvement in oral production, which can be attributed to elicitation cues applied in the robot- and 3D book-supported learning environment. Further analysis revealed a learner difference in reacting to auditory cues. Pedagogical implications for similar future efforts in using multimodal cues to enhance vocabulary learning among EFL children are also provided. Highlights: Educational robots and 3D books can form a multimodal language learning environment. Elicitation, visual, and auditory cues form a loop for task-based language learning. Cognitive, kinesthetic, and affective behaviors can result from multimodal task-based learning. Elicitation cues can effectively improve EFL vocabulary oral production.